Clinico-Aetiological Profile of Adult Epistaxis-Three Years’ Experience at a Tertiary Care Centre - Jaykumar Patel; Yojana Sharma; Priyadarshini Govindarajalu; Sohil Vadiya (Bengal Journal of Otolaryngology and Head Neck Surgery, 2022)
Introduction